2010
DOI: 10.1089/jpm.2010.0112
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Need and Opportunity: Assessing and Capitalizing on Opportunities To Expand Hospital-Based Palliative Care Services

Abstract: We present five case studies to demonstrate how successful programs identify and address institutional needs to create opportunities for palliative care program growth. These case studies can serve as models for other programs seeking to develop or expand their palliative care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…12,19,20 Despite the benefits of palliative care [18][19][20][21][22][23][24][25] and its growth in recent years, 20,25,27 it is not always available for inpatients, partly because the subspecialty palliative care workforce is not currently sufficient to reach all patients dying in hospital settings and partly because practitioners do not recognize shifts in patient trajectory indicating the need for palliative care consultation. [26][27][28][29][30][31][32] In an environment focusing on "cure," transition away from disease-modifying treatments to symptom control can seem counterintuitive. Because most Americans are likely to die in a hospital or nursing home, 20,33,34 there is a compelling need to address processes of care for actively dying patients in inpatient settings.…”
Section: Introductionmentioning
confidence: 99%
“…12,19,20 Despite the benefits of palliative care [18][19][20][21][22][23][24][25] and its growth in recent years, 20,25,27 it is not always available for inpatients, partly because the subspecialty palliative care workforce is not currently sufficient to reach all patients dying in hospital settings and partly because practitioners do not recognize shifts in patient trajectory indicating the need for palliative care consultation. [26][27][28][29][30][31][32] In an environment focusing on "cure," transition away from disease-modifying treatments to symptom control can seem counterintuitive. Because most Americans are likely to die in a hospital or nursing home, 20,33,34 there is a compelling need to address processes of care for actively dying patients in inpatient settings.…”
Section: Introductionmentioning
confidence: 99%
“…While referral to PC is probably more likely to improve patient outcomes and the circumstances around dying, rapidly identifying and addressing palliative needs and matching existing resources may be more important than increasing the availability of specialist PC services and increasing referral rates to these services. 19,20 While the information available through the patient charts was limited, our study showed that the use of endstage technologies was almost as high for patients receiving PC as those not receiving it. The 'end-of-life care culture' of both hospitals appears oriented to technologies (notably artificial fluids and oxygen), although technologies may not benefit dying patients.…”
mentioning
confidence: 83%
“…18,19 The goal for this third domain was to support skills in program development and sustainability, since palliative care programs face ongoing challenges with securing stable resources and are tasked with providing metrics to demonstrate value to their institutions. 20,21 The first 3 workshops provided opportunities to learn and practice communication skills through role-play with other learners and simulated patients. The first focused on communication skills, including introducing palliative care, responding to emotion using the NURSE pneumonic (Name, Understand, Respect, Support, Explore), 22 and eliciting a patient's narrative using ask-tell-ask 23,24 and a 7-question guide ( Table 2).…”
Section: Structure/content Of Curriculummentioning
confidence: 99%
“…18,19 The goal for this third domain was to support skills in program development and sustainability, since palliative care programs face ongoing challenges with securing stable resources and are tasked with providing metrics to demonstrate value to their institutions. 20,21…”
Section: Structure/content Of Curriculummentioning
confidence: 99%